2016
DOI: 10.1007/s12026-016-8815-9
|View full text |Cite
|
Sign up to set email alerts
|

Quadrivalent human papillomavirus vaccine and autoimmune adverse events: a case–control assessment of the vaccine adverse event reporting system (VAERS) database

Abstract: Gardasil is a quadrivalent human papillomavirus (HPV4) vaccine that was approved for use by the US Food and Drug Administration in June 2006. HPV4 vaccine is routinely recommended for administration to women in the USA who are 11–12 years old by the Advisory Committee on Immunization Practices. Previous studies suggest HPV4 vaccine administration was associated with autoimmune diseases. As a consequence, an epidemiological assessment of the vaccine adverse event reporting system database was undertaken for adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 19 publications
3
52
0
2
Order By: Relevance
“…The two studies included in the review that analysed the association of HPV vaccine and GBS did not show any increased risk of developing the syndrome among the cases compared to the controls. The study populations were women aged 18-39 years and 6-39 years [40,41]. Similar results were found in France [50].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The two studies included in the review that analysed the association of HPV vaccine and GBS did not show any increased risk of developing the syndrome among the cases compared to the controls. The study populations were women aged 18-39 years and 6-39 years [40,41]. Similar results were found in France [50].…”
Section: Discussionsupporting
confidence: 80%
“…Campylobacter jejuni ( C. jejuni ), which is one of the leading factors associated with the development of GBS, was significantly associated with the development of GBS in all seven studies that studied this association . Pneumococcal vaccine, yellow fever and human papillomavirus (HPV) in girls were other vaccines reported in the studies; none were associated with the occurrence of GBS . Other aetiological agents studied that had statistically significant association with the occurrence of GBS included: M. pneumoniae (OR = 3.95 CI 95% 1.44–13.01), Epstein Barr virus [matched Odds Ratio (mOR) 20.0 CI 95% 1.81–220.56], acute hepatitis E infection (OR = 10.5 CI 95% 1.3–82.6), herpes zoster [Hazard ratio (HR) = 16.72 CI 95% 9.47–29.53], influenza [Incidence Risk Ratio (IRR) = 8.45 CI 95% 1.79–39.77], gastrointestinal infection (RR = 41.4 CI 95% 9.0–90.8), surgery (RR = 6.28 CI 95% 4.15–9.47) respiratory infection (OR = 4.57 IC 95% 1.55–13.4) and influenza‐like illness (RI = 7.35 CI 95% 4.36–12.38) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some observational studies on the link between virus infections and SLE (Hanlon, Avenell, Aucott, & Vickers, 2014;Rasmussen, Nielsen, Houen, & Jacobsen, 2016;Zandman-Goddard et al, 2009 Guiducci, & Coffman, 2007;Fagone, Muthumani, et al, 2014;Oon, Wilson, & Wicks, 2016). Some studies find that vaccinations against virus infections can also increase risk of SLE (Agmon-Levin et al, 2014;Geier & Geier, 2017;Wang, Shao, Wang, Xu, & Zhang, 2017), which further provides some evidence for et al, 1996;Gröndal et al, 2000). Its important role is also evidenced in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Geier and Geier [22], who performed a review of cases with the serious autoimmune adverse event outcomes of the VAERS database, performed another huge work. They observed that adverse events in terms of gastroenteritis, rheumatoid arthritis, thrombocytopenia, systemic lupus erythematosus, vasculitis, alopecia, CNS demyelinating conditions, ovarian damage, and irritable bowel syndrome were associated with the quadrivalent HPV vaccine administration.…”
mentioning
confidence: 99%